Nuisance candidacies in Philippine Election Law legal history, legal analysis, and legal reform (Philippine Law Journal, 2021)
This Article traces the constitutional and legislative histories of the legal concept in Philippine election law known as nuisance candidacies as defined under Section 69 of Batas Pambansa Blg. 881, also known as the Omnibus Election Code. It analyzes its statutory definition and operationalization, and examines ways to address and reform said operationalization in the Philippine electoral system, in light of international election standards and the twin fundamental rights of participation in public life and access to opportunities to vie for public office. Nuisance candidacies are part of a long history of institutional gatekeeping in Philippine politics. However, recent Philippine Supreme Court jurisprudence has provided an opening for institutional reform that has the potential to enhance the political life and dignity of Filipinos and optimize the functioning of Philippine democracy. But a significant hurdle to these reforms is the general lack of familiarity with alternative systems to deal with nuisance candidates other than the enforcement of Section 69. This Article seeks to begin the journey in that direction.